Efektivitas Umpan Buatan untuk Mengendalikan Lalat Buah (Bactrocera spp.) pada Cabai Merah Besar (Capsicum annum) di Daerah Pondok Mangga Banjarbaru Utara - Salasiah .; Elly Liestiany; Muhammad Indar Pramudi (www.ulm.ac.id, 2018)
The intensity of fruit fly pest attacks in South Kalimantan in 2015 and 2016 showed an average intensity of attacks as muchas 66.7%, to determine the abundance of the population and interest in fruit flies in the Pondok Mangga area, NorthLoktabat Village, Banjarbaru Utara District, Banjarbaru against artificial bait ( foodlure) cucumber, watermelon, guava andstarfruit on large red chili plants so research needs to be done, using one factor RAL (six treatments and four replications).The highest number of fruit flies and the most effective in traps with the treatment of methyl eugenol anthrax as many as1463 tails. Then in the treatment of feeds made of watermelon and cucumber as many as 40 and 16 consecutive. Where thefruit fly species trapped yaittu Bactrocera dorsalis, B. carambolae, B. cucurbitae and B. umbrosa with a low diversityindex including 0.30254.